Investment Experience And Risk Tolerance Affect Investment Decision During Pan-demi Covid 19 in Indonesia (Case Study of Investment Gallery Students in South Ja-karta) - Ossi Ferli; Cindy Triyas Ambarwati; Mutiara Mutiara (Indonesia Banking School, 2022)
This research aim to know the effect of financial literacy, investment experience, and risk tolerance on in-vestment decisions of student who are members of the investment Gallery in Jakarta Selatan, aims to deter-mine whether student know financial literacy well and to find out what factors influence student in choos-ing investment decision on stock market. There are 101 samples that meet criteria in this study. The analy-sis in this study used validity, reliability, classic assumption test, and multiple linear regression. As a re-sult, financial literacy has no influence on investment decisions, but risk tolerance and investment experi-ence that can influence investment decisions. The implication of this research is that in supporting stock investment decisions in students of The Investment Gallery in South Jakarta can be done by improving the investment experience for students.